John Locke on Character Building - Wijaya, Daya Negri (ATIKAN, 2013)
ABSTRACT: Character building is a way to build a nation by focusing on the psychological development, maturation, and ethics of individual citizens. John Locke is the first thinker which is explaining the ideas above and is determined the next thinkers on nation and character building. John Locke believes that what all people have at present originally come from their experiences. The purpose of this paper is to elaborate John Lockeâs ideas on character building. His ideas seem to divide into three themes comprising the healthy body, the right mind and the healthy soul, and the formulation of character. First, John Locke believes that the strong thought is determined by the strong body. As a physician, John Locke suggests how to keep the childrenâs health: how to face the weather, how to choose the appropriate clothes, how to give the fit diet, how to have a good sleep, and how to prevent the disease. Second, after having the healthy body, John Locke tends to set the right mind and the healthy soul by parent at the time of infancy. What is the habit which is settled by parent, it would be childâs habit. Third, childâs character is formed based on parentâs example. They would be role models for their child. The child tends to imitate the parentâs activities.KEY WORD: John Locke, education process, character building, roles of teacher and parent, healthy body, rational creature, and good citizens.IKHTISAR: Artikel ini berjudul âJohn Locke tentang Pembangunan Karakterâ. Pembangunan karakter adalah cara untuk membangun bangsa dengan berfokus pada perkembangan psikologis, kematangan, dan etika warga negara. John Locke adalah pemikir pertama yang menjelaskan ide di atas dan diperkuat oleh para pemikir berikutnya tentang pembangunan karakter dan bangsa. John Locke percaya bahwa apa yang semua orang punya saat ini awalnya berasal dari pengalaman mereka. Tujuan makalah ini adalah untuk menguraikan gagasan John Locke tentang pembentukan karakter. Ide-ide John Locke tampaknya dapat dibagi menjadi tiga tema yang terdiri dari: tubuh yang sehat, pikiran yang benar dan jiwa yang sehat, serta perumusan karakter. Pertama, John Locke percaya bahwa pikiran yang kuat ditentukan oleh tubuh yang kuat. Sebagai seorang dokter, John Locke menyarankan bagaimana menjaga kesehatan anak-anak: bagaimana menghadapi cuaca, bagaimana memilih pakaian yang tepat, bagaimana memberikan diet yang sehat, bagaimana cara tidur yang baik, dan bagaimana mencegah penyakit. Kedua, setelah memiliki tubuh yang sehat, John Locke cenderung untuk mengatur pikiran yang waras dan jiwa yang sehat oleh orang tua pada saat bayi. Apa saja kebiasaan yang dilakukan oleh orang tua akan menjadi kebiasaan anak. Ketiga, karakter anak terbentuk berdasarkan contoh orang tua. Mereka akan menjadi panutan bagi anak-anak mereka. Anak cenderung meniru kegiatan orang tua.Â  KATA KUNCI: John Locke, proses pendidikan, pembentukan karakter, peran guru dan orang tua, tubuh yang sehat, makhluk rasional, dan warga negara yang baik.About the Author: Daya Negri Wijaya is a Student of M.A. (Master of Arts) History at University of Sunderland, Chester Road, Sunderland, SR1 3SD, United Kingdom. For academic purposes, he can be contacted via his e-mail at: dayawijaya15@yahoo.comHow to cite this article? Wijaya, Daya Negri. (2013). âJohn Locke on Character Buildingâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.3(2) December, pp.115-128. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung and FKIP UNSUR in Cianjur, West Java, ISSN 2088-1290. Chronicle of the article: Accepted (October 20, 2013); Revised (November 20, 2013); and Published (December 15, 2013).